Know Your Counterparts: The Importance of Wording for Stakeholder Communication in Social Franchise Enterprises - Arne Bergfeld; Carolin Plagmann; Eva Lutz (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2020)
Social enterprises pursue a dual mission: on the one hand, they strive for social purpose, while on the other, they try to achieve economic stability despite scarce resources. To achieve the dual mission, social enterprises avail themselves of both for-profit and non-profit institutional logics. Due to this combination of multiple institutional logics, such enterprises can be classified as hybrid organizations. This study focuses on these organizations and investigates tensions between social enterprises and various stakeholder groups caused by the use of commercial logics within the social sector. In particular, we examine the perception of commercial versus social welfare logics by various stakeholder groups, and investigate the effects on organizational communication. Our study is centered on social franchise enterprises. We use an exploratory qualitative research approach based on semi-structured interviews with 21 social franchisors and social franchisees of seven social franchise enterprises. Our main results suggest that the use of commercial logics in the social sector tends to decrease the legitimacy of social franchise enterprises in the eyes of internal stakeholders, the general public, and various (but not all) external stakeholder groups. Many stakeholders of social franchise enterprises show a strong aversion to commercial logics, and particularly to commercial terminology. Overall, we conclude that social franchise enterprises very consciously apply commercial and social welfare logics and use alternative terminology where necessary to retain legitimacy and prevent tensions.
Keywords: 300; Non-profit; Hybridity; Communication; Institutional logics; Social franchising; Legitimacy